2022
DOI: 10.1039/d2me00084a
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene-glycol-modified zwitterionic polymer assisted protein aggregation arrest and refolding

Abstract: Protein aggregation limits the development of protein-based drugs, and leads to neurological disorders. In this study, the zwitterionic polymer, poly-sulfobetaine (p-SPB), was modified using the polyethylene glycol (PEG), and exhibited...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that PEG facilitates the suppression of protein aggregation owing to its ability to strongly interact with thermally unfolded proteins, thus protecting them from aggregation-inducing collisions. [31,42] Hence, a synergistic effect is observed where PEG and PLLSA work together to realize higher activity than those of both the individual components. The secondary structure of in-sulin was retained, and the CD spectra of the insulin combined with micelles were comparable to those of the native protein (Figure S21, Supporting Information).…”
Section: Protein Protection Studiesmentioning
confidence: 99%
“…Previous studies have reported that PEG facilitates the suppression of protein aggregation owing to its ability to strongly interact with thermally unfolded proteins, thus protecting them from aggregation-inducing collisions. [31,42] Hence, a synergistic effect is observed where PEG and PLLSA work together to realize higher activity than those of both the individual components. The secondary structure of in-sulin was retained, and the CD spectra of the insulin combined with micelles were comparable to those of the native protein (Figure S21, Supporting Information).…”
Section: Protein Protection Studiesmentioning
confidence: 99%
“…In our previous studies, we showed that poly-sulfobetaine (poly-SPB), a zwitterionic polymer, exhibits good efficiency in protecting proteins from thermal denaturation. [19][20][21][22][23][24] A number of poly-SPB derivatives have been prepared by adding hydrophobic monomers, transforming into nanogels, or preparing gra polymers to achieve higher activity. Although previously known agents and zwitterionic polymers have remarkable abilities to protect proteins, a major drawback of this process is the inability to separate proteins from the stabilizing agents.…”
Section: Introductionmentioning
confidence: 99%
“…Many classes of small molecules, such as polyamines, vitamins, polyphenols, peptides, and nondetergent sulfobetaines, have been successfully applied for this purpose. Additionally, a few polymers with relatively good performance have recently been reported. In particular, zwitterionic polymers have been shown to inhibit the aggregation of lysozyme under thermal stress and facilitate the retention of enzymatic activity. However, very high concentrations of zwitterionic polymers are required to achieve good efficiency, which is not feasible for industrial or clinical applications. , Hence, for applications in protein processing and protein therapeutics, it is highly desirable to develop polymeric systems with significantly improved efficacy.…”
Section: Introductionmentioning
confidence: 99%